Financial Performance Management of The Bank - Setiadi, Pompong Budi (Jurnal Aplikasi Manajemen, 2014)
The objective of this paper is to provide a theoretical review and a complete description about financial performance management of the bank. Method used in this review is the study of literature or theoretical studies. Result of this review indicates that (1) bank's financial performance is measured with some parameters such as Earning per Share (EPS), Return on Equity (ROE), Return on Asset (ROA), revenue growth, loan growth, net income growth compared to profit planning, saving growth, Return on Investment (ROI), and Net Present Value (NPV); (2) financial parameters are measured depending on accounting methods or treatments used to prepare the financial statement of the bank; (3) Financial ratio is the comparison of two variables of financial data to explain the relationship between those two; (4) Some financial ratios are used by an analyst to measure financialperformance, such as: Profitability Ratio, Liquidity Ratio, Solvability Ratio, Activity Ratio, Growth Ratio, Market Value Ratio, and Economic Value Added; (5) The analysis over these ratios is fulfilling not only the internal interest but also external interest of the firm, because it is useful (a) to compare the firm with other firm at similar business sector, (b) to compare with other at different business, and (c) to compare the performance at different period of time.